AN ANALYSIS ON KNOWLEDGE, PERCEPTION AND SOCIOCULTURAL FACTORS AFFECTING MOTHER’S BEHAVIOR IN GIVING BREASTFEED-SUPPLEMENT MEAL - Yulianto Yulianto; Yufi Aris Lestari; Nur Chasanah; Pipit Festy; Nasrul Hadi (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
The administration of breastfeed-supplement meal to less than 6-month age baby occurs because mother considers that breastfeed-supplement meal is better than breastfeed. The objective of research is to analyze knowledge, perception and sociocultural factors affecting mother’s behavior in giving breastfeed-supplement meal in less than 6-month age baby. The research design used was correlational analytical one with crosssectional approach. The population of research included all mothers of 7-12 month age baby, consisting of 40 mothers. The sample consisted of 37 respondents, taken using simple random sampling technique. Data was collected using questionnaire and tested using linear regression, as well as presented in the form of frequency distribution frequency. From the result of regression test, it could be found R value = 0.717, indicating that there is a fairly strong relationship between independent and dependent variables, while coefficient of determinacy or R square value was 0.514 or 51.4%, meaning that independent variable contributed to dependent variable by 51.4%. Mothers’ good knowledge on breastfeed-supplement meal can affect their behavior in giving breastfeed-supplement meal because through such knowledge, mothers can recognize and understand how to give breastfeed-supplement meal appropriately to babies. Similarly, perception and socio-cultural factors developing in family or community environment can affect mothers’ behavior